Tindak Tutur Ekspresif Pada Film Kukira Kau Rumah - Rahmawati; Usman; Sakaria (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research aims to describe the form and function of expressive speech acts in the film Kukira Kau Rumah. This type of research is a descriptive qualitative research, the data source of this research is the film Kukira Kau Rumah by Monty Tiwa, Imam Salimy and Umay Shahab. The data collection technique was carried out using the method of listening technique and note taking technique. This research instrument consists of the main instrument, namely the researcher and supporting instruments such as mobile phones, leptop and data cards. First, the forms of expressive speech acts in the film Kukira Kau Rumah are literal direct speech acts, literal indirect speech acts, non-literal direct speech acts, and literal indirect speech acts. Second, the function of expressive speech acts in the film Kukira Kau Rumah is the function of expressing gratitude, the function of congratulating/praising, the function of expressing apology, the function of expressing sympathy, the function of expressing anger, and the function of greeting.